Netralitas Gubernur dalam Pemilihan Umum - Muhammad Abdul Aziz; Tomy Michael (ADALAH, 2020)
Abstract:The rule of law is obliged to uphold the values or principles that guide the implementation of the government and its law enforcement, one of which is the principle of democracy. The obvious application of the principle of democracy is elections. Election is a process of holding people's sovereignty in order to fill positions in a government based on direct, general, free, confidential, honest, and fair. In the general election it is expected that the election participants will be neutral in choosing a candidate for leader or representative of the people. Whereas many public officials such as the Governor use power to help their partners in various ways, one of which is ensuring their support for their counterparts. Because the governor's voice greatly affects the community as well as the State Civil Apparatus.Keywords: Election, Neutrality, GovernorAbstrak:Negara hukum diharuskan untuk menjunjung nilai-nilai atau asas-asas yang menjadi pedoman penyelenggaran pemerintah dan penegakan hukumnya, yang salah satunya adalah asas demokrasi. Penerapan asas demokrasi yang nampak jelas ialah pemilihan umum. Pemilihan umum merupakan proses penyelenggaran kedaulatan rakyat dalam rangka mengisi jabatan-jabatan dalam suatu pemerintahan yang berasaskan langsung, umum, bebas, rahasia, jujur, dan adil. Dalam pemilihan umum diharapkan peserta pemilu bersikap Netral dalam memilih calon pemimpin atau wakil rakyat. Sedangkan banyak sekali pejabat publik seperti Gubernur yang menggunakan kekuasaan untuk membantu rekan separtainya dengan berbagai cara, yang salah satunya memastikan dukungannya terhadap rekan separtainya. Dikarenakan suara gubernur sangat mempengaruhi masyarakat maupun para Aparatur Sipin Negara.Kata Kunci: Pemilu, Netralitas, Gubernur